Distribution of waiting time between two successive aftershocks from modified Omori's law. (4th November 2019) - Tamori, Hiroyoshi; Yano, Ryosuke
Abstract: The primary aim of this letter is the derivation of the distribution of the waiting time between two successive aftershocks from the modified Omori's law. We also propose two models. One model is the elapsed time-accumulation (ETA) model, and the Non-homogeneous Poisson Process (NPP) model. Using these two models, we confirm the conditions under which the distributions of the waiting time obtained follow the Zipf-Mandelbrot law.